(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to collect the base line information from the Pantja goat rearers regarding to constraints being perceived by goat keepers in goat rearing of Udham Singh Nagar and Nainital districts of Tarai region of the Uttarakhand. A total 645 respondents were interviewed from one hundred thirteen villages with the help of the structured interview schedule to understand the constraints faced by the goat rearers. The results of present study revealed that the lack of credit and insurance facilities were the foremost serious constraints faced by goat rearers followed by lack of veterinary services, inadequate availability of quality breeding buck, lack of organized market of goats, shortage of feed and fodder and poor knowledge of scientific goat rearing practices. It may be concluded that the socio-economic condition of goat rearers can be improved by facilitate long term credit facility on minimum interest rates and insurance of goats and also providing scientific guidance about goat rearing, which will not only generate income for their livelihood but also contribute much to the nutritional and health security.